Controlled Delivery of Celecoxib-β-Cyclodextrin Complexes from the Nanostructured Titanium Dioxide Layers - Magdalena Jarosz; Jakub Latosiński; Paweł Gumułka; Monika Dąbrowska; Mariusz Kępczyński; Grzegorz Dariusz Sulka; Małgorzata Starek (MDPI AG, 2023)
Considering the potential of nanostructured titanium dioxide layers as drug delivery systems, it is advisable to indicate the possibility of creating a functional drug delivery system based on anodic TiO2 for celecoxib as an alternative anti-inflammatory drug and its inclusion complex with β-cyclodextrin. First, the optimal composition of celecoxib-β-cyclodextrin complexes was synthesized and determined. The effectiveness of the complexation was quantified using isothermal titration calorimetry (ITC), differential scanning calorimetry (DSC), infrared spectroscopy (FT-IR) nuclear magnetic resonance (1H NMR), and scanning electron microscopy (SEM). Then, nanostructured titanium dioxide layers (TiO2) were synthesized using the electrochemical oxidation technique. The TiO2 layers with pore diameters of 60 nm and layer thickness of 1.60 µm were used as drug delivery systems. The samples were modified with pure celecoxib and the β-cyclodextrin-celecoxib complex. The release profiles shown effective drug release from such layers during 24 h. After the initial burst release, the drug was continuously released from the pores. The presented results confirm that the use of nanostructured TiO2 as a drug delivery system can be effectively used in more complicated systems composed of β-cyclodextrin-celecoxib complexes, making such drugs available for pain treatment, e.g., for orthopedic surgeries.